Novel approach of determining the best absorbent for the quantification of aqueous analyte using laser-induced breakdown spectroscopy (LIBS): Zeolite versus bentonite - Ahmad, Khairunnas; Prasetyo, Siswoyo; Zaitun, Zaitun; Hajashafira, Ceudah (Narra X, 2024)
Heavy metal pollution, particularly from sources like lead (Pb), poses significant risks to human health and the environment. Monitoring heavy metal contamination is essential, and Laser-Induced Breakdown Spectroscopy (LIBS) is a promising technique for this purpose. However, matrix effects, particularly from adsorbent materials like zeolite and bentonite, can influence the accuracy of LIBS measurements. This study aims to investigate the matrix effects of zeolite and bentonite on the measurement of Pb using LIBS, focusing on how the physical and chemical properties of these materials impact the detection of Pb emission lines. Zeolite and bentonite samples were prepared by grinding and sieving to obtain powders with particle sizes less than 74 µm. These powders were then mixed with varying weights of lead nitrate (Pb(NO3)2) and pelletized to create uniform samples. The pellets were analyzed using LIBS, employing a Q-switched Nd:YAG laser. The emitted plasma light was collected and transmitted to a spectrometer equipped with an intensified charge-coupled device (ICCD) camera. The spectral data were accumulated over 10 laser shots to ensure accuracy in detecting the elemental composition. The study found that the matrix effects from bentonite and zeolite significantly influenced the intensity and clarity of Pb emission lines. Bentonite showed a stronger influence on Pb detection, particularly due to the presence of Fe and Ti, which affected the Pb I lines at 405.8 nm and 368.3 nm. In contrast, zeolite exhibited fewer interferences, but the matrix effect was still evident. The matrix effects of zeolite and bentonite, derived from their physical and chemical properties, significantly impact Pb measurements using LIBS. Further research into different adsorbents and their matrix effects is warranted to improve the accuracy of LIBS in heavy metal analysis.